COMPARATIVE ANALYSIS OF EFFICIENCY OF NANOSTRUCTURED AND POLYURETHANE STENTS FOR DRAINAGE OF THE UPPER URINARY TRACT IN EXPERIMENT - S. V. Shkodkin; M. I. Kogan; Y. B. Idashkin; Y. N. Kobyakova; L. N. Nichikova (Вестник трансплантологии и искусственных органов)
This article presents the results of a pilot study of experimental stent in comparison to traditionally used. Experi- ments were performed on 20 adult male rabbits weighing 4350–4580 grams. The main study group (10 animals) was performed an experimental unilateral implantation of the stent, as a control (10 animals) was performed a unilateral stent implantation «White-star standart» (Company Urotech, Germany), of the same diameter. The observation period was 1 month. There were performed laboratory tests of blood and urine, as well as morpholo- gical examination of the kidneys and ureters. We obtain statistically significant benefits of using an experimental stent.